Designing Performance Assessment for Ethnomathematics Project-Based Learning to Assess University Students’ Mathematical Thinking Skills - Ulya, Himmatul; Rahayu, Ratri; Sa’dijah, Cholis; Qohar, Abd; Saad, Muhamad Ikhwan Mat (Jurnal Pendidikan MIPA, 2024)
The skills involved in the mathematical thinking process are crucial for university students pursuing Mathematics Education. However, most of them lack proficiency in seeing patterns while addressing an issue and articulating the problem in mathematical terms. The objectives of this research are (1) to analyze students' mathematical thinking process skills; (2) to ascertain students' expectations regarding the learning process and assessment in Ethnomathematical education; (3) to develop a performance assessment model design; (4) to evaluate the quality of the performance assessment model within Ethnomathematics-based Project-based Learning (PjBL) for measuring students' mathematical thinking process skills; and (5) to report the outcomes of measuring students' mathematical thinking process skills. This study employs a research and development (R&D) design. This study's population comprises all 6th-semester students enrolled in the Mathematics Education program at Muria Kudus University. The research sample was obtained by a saturation sampling procedure, comprising 107 students. The study instruments employed consist of assessment tools designed to evaluate students' mathematics cognitive processing skills. The acquired data were analyzed descriptively. The research findings indicate that: (1) students' mathematical thinking process skills are suboptimal, with a mean value of 54.14%; (2) students desire greater engagement in an active learning process that connects to real-life situations and cultural contexts, incorporating assessments that reflect individual performance; (3) a performance assessment model design for Ethnomathematics-based Project-Based Learning (PjBL) has been developed, encompassing objectives, components, instruments, syntax, and model guidelines. The created performance assessment approach for ethnomathematics-based project-based learning is both valid and reliable, and the evaluation of mathematical thinking process abilities demonstrates exceptional outcomes. This study suggests the necessity of implementing the ethnomathematics-based Project-Based Learning (PJBL) performance evaluation model to enhance students' mathematical thinking skills through an active, contextual, and culturally relevant method.         Keywords: ethnomathematics, performance assessment, pjbl, project-based learning.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1281-1296